Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1021/bi990510+
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble β-Sheet Models Which Self-Assemble into Fibrillar Structures

Abstract: Self-assembly of beta-sheet domains resulting in the formation of pathogenic, fibrillar protein aggregates (amyloids) is a characteristic feature of various medical disorders. These include neurodegenerative diseases, such as Alzheimer's, Huntington's, and Creutzfeldt-Jacob's. A significant problem in studying such aggregation processes is the poor solubility of these beta-sheet complexes. The present work describes water-soluble de novo beta-sheet peptides which self-assemble into fibrillar structures. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
131
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(142 citation statements)
references
References 42 publications
9
131
0
2
Order By: Relevance
“…4 Structure-activity studies revealed that peptides containing the highly hydrophobic 25-35 region formed stable aggregates and mediated neuronal death by necrosis or apoptosis. 5,6,7 The truncated A␤ [25][26][27][28][29][30][31][32][33][34][35] fragment includes extracellular and intramembrane residues that have been reported to represent an active region of A␤. 8 In vivo, two nontransgenic rodent models of AD have been studied to analyze the molecular, morphological, and behavioral consequences of amyloid toxicity: the infusion of A␤ 1-40/42 protein and the injection of preaggregated A␤ [25][26][27][28][29][30][31][32][33][34][35] peptide.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…4 Structure-activity studies revealed that peptides containing the highly hydrophobic 25-35 region formed stable aggregates and mediated neuronal death by necrosis or apoptosis. 5,6,7 The truncated A␤ [25][26][27][28][29][30][31][32][33][34][35] fragment includes extracellular and intramembrane residues that have been reported to represent an active region of A␤. 8 In vivo, two nontransgenic rodent models of AD have been studied to analyze the molecular, morphological, and behavioral consequences of amyloid toxicity: the infusion of A␤ 1-40/42 protein and the injection of preaggregated A␤ [25][26][27][28][29][30][31][32][33][34][35] peptide.…”
mentioning
confidence: 99%
“…These models have led to highly pertinent pathomimetic observations and provide complementary approaches to the numerous transgenic mouse lines developed as AD models. In particular, at 1 week after A␤ [25][26][27][28][29][30][31][32][33][34][35] injection, reactive gliosis was observed in the rat hippocampus, 9 caspase-3 activity was induced in the hippocampus and cortex, 9 a reduction in the number of neurons was measured in the CA1 or CA3 hippocampal area, 9 -11 and significant oxidative stress was observed. [11][12][13] Nonetheless, this amyloid toxicity model remains controversial with respect to AD.…”
mentioning
confidence: 99%
See 3 more Smart Citations